2015
DOI: 10.1097/rti.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Acute Pulmonary Embolism With Computed Tomography

Abstract: Acute pulmonary embolism is recognized as a difficult diagnosis to make. It is potentially fatal if undiagnosed, yet increasing referral rates for imaging and falling diagnostic yields are topics which have attracted much attention. For patients in the emergency department with suspected pulmonary embolism, computed tomography pulmonary angiography (CTPA) is the test of choice for most physicians, and hence radiology has a key role to play in the patient pathway. This review will outline key aspects of the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…contrast enhancement of the pulmonary arteries, and subjective image quality is more closely related to vessel enhancement than to noise. 9,36,41 There is a statistically significant negative correlation reported between mean/peak vessel enhancement and patient size. 41,42 Lowering the kVp can increase HU in the pulmonary arteries, making them appear brighter, because the attenuation of the beam increases as the beam energy reaches the k-edge of iodine.…”
Section: Challenges Of Imaging In Obesitymentioning
confidence: 94%
See 1 more Smart Citation
“…contrast enhancement of the pulmonary arteries, and subjective image quality is more closely related to vessel enhancement than to noise. 9,36,41 There is a statistically significant negative correlation reported between mean/peak vessel enhancement and patient size. 41,42 Lowering the kVp can increase HU in the pulmonary arteries, making them appear brighter, because the attenuation of the beam increases as the beam energy reaches the k-edge of iodine.…”
Section: Challenges Of Imaging In Obesitymentioning
confidence: 94%
“…PE was identified in 22.6% of CTPAs in the PIOPED II study, but its incidence has been around 14-18%, and as low as 9%, in more recent studies. [35][36][37][38] The accuracy of CTPA in overweight and obese patients is generally good (Figure 1). Some studies have shown no difference in subjective image quality, diagnostic confidence, or diagnostic accuracy between obese and non-obese patients.…”
Section: Challenges Of Imaging In Obesitymentioning
confidence: 95%
“…Computed tomography pulmonary angiography (CTPA) is increasingly used in the diagnosis of patients with suspected pulmonary embolism (PE) due to its high sensitivity and specificity for detecting segmental and subsegmental PE (1)(2)(3)(4)(5). However, the high radiation dose associated with the increased use of CTPA examinations has raised concerns leading to the paradigm shift of developing optimal CTPA protocols to lower radiation dose while still achieving diagnostic images.…”
Section: Introductionmentioning
confidence: 99%
“…In another CT study, it was also documented that coronary atherosclerosis was not uncommon in asymptomatic SSc patients [58] . Finally, CT scan is the technique of choice for assessment of pulmonary embolism and pulmonary hypertension secondary due to recurrent pulmonary emboli [59] .…”
Section: Single-photon Emission Computed Tomographymentioning
confidence: 99%